Kepemimpinan Pendidikan Bu Nyai dalam Pengambilan Keputusan dan Motivasi Pemimpin di Pesantren Al-Qur’an - Aminatu Zuhriyah; Zaenal Arifin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
The role of leadership is very strategic and vital in an organization as one of the determinants of success. Both men and women have the potential to lead an organization. Inclusive leaders are leaders who have openness, are flexible, sociable, and can accommodate various kinds of differences and, of course, must be able to absorb all existing aspirations. From here, this study aims to determine the decision-making and motivation of Bu Nyai P3TQ Al-Hidayah. This research uses the type of case study research which is part of a qualitative method that wants to explore a particular case in more depth. The result of this study is that the decision-making applied consists of several styles, namely authoritarian, directive, and analytic, according to the problems being faced, and the motivation of the leader is done by building good communication between caregivers and administrators. In contrast, various kinds of motivation are applied in the form of positive and negative motivation.